Modelling the cost‐effectiveness of adopting risk‐stratified approaches to extended screening intervals in the national diabetic retinopathy screening programme in Scotland. Issue 7 (11th May 2016) - Scotland, G.; McKeigue, P.; Philip, S.; Leese, G. P.; Olson, J. A.; Looker, H. C.; Colhoun, H. M.; Javanbakht, M.
Abstract: Aims: To assess the cost‐effectiveness of adopting risk‐stratified approaches to extended screening intervals in the national diabetic retinopathy screening programme in Scotland. Methods: A continuous‐time hidden Markov model was fitted to national longitudinal screening data to derive transition probabilities between observed non‐referable and referable retinopathy states. These were incorporated in a decision model simulating progression, costs and visual acuity outcomes for a synthetic cohort with a covariate distribution matching that of the Scottish diabetic screening population. The cost‐effectiveness of adopting extended (2–year) screening for groups with no observed retinopathy was then assessed over a 30–year time horizon. Results: Individuals with a current grade of no retinopathy on two consecutive screening episodes face the lowest risk of progressing to referable disease. For the cohort as a whole, the incremental cost per quality‐adjusted life year gained for annual vs. biennial screening ranged from approximately £74 000 (for those with no retinopathy and a prior observed grade of mild or observable background retinopathy) to approximately £232 000 per quality‐adjusted life year gained (for those with no retinopathy on two consecutive screening episodes). The corresponding incremental cost‐effectiveness ratios in the subgroup with Type 1 diabetes were substantially lower; approximately £22 000 to £85 000 per quality‐adjusted life year gained, respectively. Conclusions: Biennial screening for individuals with diabetes who have no retinopathy is likely to deliver significant savings for a very small increase in the risk of adverse visual acuity and quality of life outcomes. There is greater uncertainty regarding the long‐term cost‐effectiveness of adopting biennial screening in younger people with Type 1 diabetes. What's new?: A microsimulation model of the diabetic retinopathy screening and treatment pathways in Scotland was developed; incorporating risks of progression estimated from contemporary, longitudinal, population‐based screening outcome data. The adoption of biennial screening intervals for those with diabetes and no diabetic retinopathy is likely to be cost‐effective. There is greater uncertainty surrounding the long‐term cost‐effectiveness of biennial screening in younger people with Type 1 diabetes and no retinopathy, due to the higher long‐term cumulative risk of developing interval referable disease, and a lower competing risk of death from all causes.